Characteristics and Management of Superior Semicircular Canal Dehiscence - Yew, Andrew; Zarinkhou, Golmah; Spasic, Marko; Trang, Andy; Gopen, Quinton; Yang, Isaac (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objectives To review the characteristic symptoms of superior semicircular canal dehiscence, testing and imaging of the disease, and the current treatment and surgical options.Results and Conclusions Symptoms of superior semicircular canal dehiscence (SSCD) include autophony, inner ear conductive hearing loss, Hennebert sign, and sound-induced episodic vertigo and disequilibrium (Tullio phenomenon), among others. Potential etiologies noted for canal dehiscence include possible developmental abnormalities, congenital defects, chronic otitis media with cholesteatoma, fibrous dysplasia, and high-riding jugular bulb. Computed tomography (CT), vestibular evoked myogenic potentials, Valsalva maneuvers, and certain auditory testing may prove useful in the detection and evaluation of dehiscence syndrome. Multislice temporal bone CT examinations are normally performed with fine-cut (0.5- to 0.6-mm) collimation reformatted to the plane of the superior canal such that images are parallel and orthogonal to the plane. For the successful alleviation of auditory and vestibular symptoms, a bony dehiscence can be surgically resurfaced, plugged, or capped through a middle fossa craniotomy or the transmastoid approach. SSCD should only be surgically treated in patients who exhibit clinical manifestations.
Keywords: superior semicircular canal dehiscence syndrome; vertigo; hearing loss; autophony; Tullio phenomenon